INDEK GLIKEMIK UWI, GADUNG DAN TALAS YANG DIBERIKAN PADA TIKUS - Ika Puspita Sari; Endang Lukitaningsih; Rumiyati Rumiyati; Irfan Muris Setiawan (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
The aim of the study was the determination of glycaemic index (GI) of local tubers such as Uwi (Dioscorea alata), Gadung (Dioscorea hispida), dan Talas (Colocasia esculenta). Tubers were prepared as raw flour which were administered orally to the rats. Blood were taken at 0; 0,5; 1 and 2 hour after tubers administration. The dose was 2,5 kg/kg body weight (BW) whereas glucose was administered as a standart treatment. Area Under Curve (AUC) was calculated after plotting the graph of time versus glucose levels. Glucose levels were determined using GOD-PAP kit. GI values were calculated as a ratio of AUC (0-2hr) of tubers to glucose. Porang was moderate while the other tubers were low GI.